The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/acp.3142
|View full text |Cite
|
Sign up to set email alerts
|

State‐of‐the‐Art Research into Multimedia Learning: A Commentary on Mayer's Handbook of Multimedia Learning

Abstract: This article reviews the research into multimedia learning through the lens of a recently updated Handbook of Multimedia Learning edited by Richard Mayer. By examining the theories underpinning the research and the major experimental findings, a number of conclusions emerged. Firstly, the major theories and models guiding the research are well accepted and based on classical memory research, although there is a need to extend them to the affective domain. Secondly, most of the boundary conditions for effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Analysing the participant feedback in detail, showed that 75% of students indicated via the survey that they "found the use of multiple forms of media (3DP and app) effective". This is supportive of not only work in paramedics, but the general work in mixed reality that indicates combining of multiple forms of media can be helpful to students' learning (Ayres, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing the participant feedback in detail, showed that 75% of students indicated via the survey that they "found the use of multiple forms of media (3DP and app) effective". This is supportive of not only work in paramedics, but the general work in mixed reality that indicates combining of multiple forms of media can be helpful to students' learning (Ayres, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is notably true for paramedic science in Australia (Hou, Rego, & Service, 2013). However, universities in general are lagging behind in innovative pedagogy especially when students are studying from a distance, with most prior work formed around two-dimensional (2D) words and pictures, with less attention given to complex skills learning environments using interactive visualisations, games, and simulations (Ayres, 2015). Brydges et al (2015) explore these issues from a self-regulated learning approach and recommend learning design should support and help prepare individuals for future learning by assisting learners with self-regulated learning through simulation including obervation (e.g., watching a video), emulation (e.g., imitating the instructional video), measuring self-control (e.g., goal setting), and observational measure of learning transfer.…”
Section: Changing Educational Delivery For Health Disciplines and Parmentioning
confidence: 99%
“…However, universities in general are lagging behind in innovative pedagogy, especially when students are studying from a distance [9], with most prior work formed around two-dimensional (2D) words and pictures [36], with less attention given to complex skills learning environments using interactive visualizations, games, and simulations [20]. Brydges et al [37] explore these issues from a self-regulated learning perspective and recommend that learning design should support and help prepare individuals for future learning by assisting learners with self-regulated learning through simulation, including observation (e.g., watching a video), emulation (e.g., imitating the instructional video), measuring self-control (e.g., goal setting), and an observational measure of learning transfer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, universities in general are lagging in innovative pedagogy especially when students are studying from a distance, with most prior work formed around 2d words and pictures, and less attention given to complex skills learning environments using interactive visualizations, games and simulations [8].…”
Section: Introductionmentioning
confidence: 99%